Soy Milk with Cinnamon and Green Grass Jelly: An Alternative Snack for Type 2 Diabetes Patients - Nurul Hindaryani; Erlyna Jayeng Wijayanti; Nuning Marina Pengge; Christine I. Reyes (International Journal of Advanced Health Science and Technology, 2025)
ABSTRACT Soy juice or also known as soy milk is in great demand by people who are allergic to cow's milk. Existing soy milk usually smells a little languorous so it is less desirable, to anticipate this by adding pandan leaves when boiling it or by adding synthetic essences. In this research, soy milk will be added with ingredients that have never been used and combined, namely cinnamon and green grass jelly. This research aims to evaluate the acceptability and nutritional benefits of soy milk with cinnamon and green grass jelly as an alternative snack for type 2 diabetes patients. The research design used is an experiment by giving treatment to samples to find out the acceptability of the product after being treated. The product made was carried out 3 treatments on the composition of ingredients (weight) with the ratio of Soy Milk : Cinnamon Powder : Green grass jelly as follows : Formulation 1 (SC01) = 150 : 1 : 50, Formulation 2 (SC02) = 150 : 1,5 : 50, Formulation 3 (SC03) = 150 : 2 : 50. Tests on soy milk with the addition of cinnamon powder and green grass jelly were carried out through 2 types of tests, namely subjective tests and objective tests. Subjective tests (organoleptic tests) were conducted with a target of 30 trained panelists using a hedonic scale to analyze the level of liking based on color, taste, aroma, and texture. As for objective tests using gravimetric tests in the laboratory by looking at the fiber and chromium content in soy milk with the addition of cinnamon powder and green grass jelly. Based on the results of the Organoleptic Test on all formulas, the most preferred is formula SC03 with 17 panelists/56.7%, the aroma of formula SC02 with 18 panelists/60%, the taste of formula SC02 with 14 panelists/46.6%, the viscosity/texture of formula SC02 and SC03 with 15 panelists/50%. INDEX TERMS Acceptability, Type 2 diabetes mellitus, Chromium level, Fiber level, Soy milk, Cinnamon, Green grass jelly